S115 Improving curative-intent treatment rates in early stage lung cancer – results from 775 patients in the NLCA spotlight audit. (December 2018) - Navani, N; Harden, S; Khakwani, A; Wood, N; Woolhouse, I; Beckett, P
Abstract : Background: One possible explanation for poor survival in lung cancer patients in the UK is under-utilisation of curative-intent treatment. We carried out a spotlight audit to understand why eligible patients do not receive surgical treatment and whether national guidelines for assessment of early-stage lung cancer were being adhered to. Methods: Details of patients in England with stage I/II NSCLC and a performance status of 0–1 who did not undergo surgical treatment were extracted from the NLCA dataset and used to populate a web-based portal developed in conjunction with the National Cancer Registration and Analysis Service (NCRAS). Trusts were invited to populate their cases with additional data. Results: 82 of 142 trusts in England took part in the audit and data on 775 patients was suitable for analysis (67% stage I and 33% stage II). 46% of patients did receive treatment with curative intent in the form of SABR or radical radiotherapy (including CHART). 8% received other anti-cancer therapy, and 46% received best supportive care. As expected, age over 75 independently predicted best supportive care, even after other factors associated with age (such as co-morbidity and PS) are taken into account. 31% of patients did not have surgery owing to patient choice and, of these, 66% preferred SABR or other radical radiotherapy, while the remainder elected for no treatment. Only 2% of patients had a second surgical opinion, 14% had a CPEX, 34% had an echocardiogram and 11% had a V/Q scan. Very few patients had a shuttle walk test, or had thoracoscore or a formal cardiac risk assessed. 1 year survival for patients having best supportive care was 37%, for SABR it was 67%, for radical radiotherapy it was 45% and for those undergoing palliative radiotherapy was 27%. After adjustment for age, PS, stage, deprivation index and comorbidity index (ACE-27), both SABR and radical radiotherapy improved survival compared with best supportive care. Conclusions: Although nearly half the patients did receive an alternative treatment with curative intent, patient choice is a common reason for not receiving surgery. It is crucial that patients are assessed according to best practice and that information about their options is delivered and discussed appropriately.